Some aspects of syntax of 5-6 year old children: a descriptive study in Kannada - Prema KS (Journal of All India Institute of Speech and Hearing, 1970)
An attempt was made in this study to describe some of the syntactic patterns, of 5-6 year old children. Four children were selected for the study in the age range' of 5-6 years. All the children were from Brahmin families, with Kannada as their native language and they were from" middle class" group.